KONDISI KUALITAS AIR SUMUR PENDUDUK DI WILAYAH GENANGAN SEMBURAN LUMPUR SIDOARJO - Yudo, Satmoko (Jurnal Air Indonesia, 2009)
Sidoardjo mudflow has been occuring since 2006. This disaster is the first incident in Indonesia which has such a broad impact, like the settlements, fields, roads and other buildings submerged, resulting in enormous losses. Besides damaging the existing infrastructure in the area, the mud flow is also causing environmental damage, particularly contamination of ground water community. To find out how much the impact of the mud flow to the water quality community, carried out observations and surveys of well water quality conditions of the communities around the location of the mud puddles. In this paper provided an alternative drinking water treatment technology can be applied in this area.Ã‚Â Keywords: Lapindo mud, environmental degradation, pollution of well water quality, alternative water treatment technologies